Requisite Omega-3 HUFA Biomarker Thresholds for Preventing Murine Lupus Flaring - Wierenga, Kathryn A.; Strakovsky, Rita S.; Benninghoff, Abby D.; Rajasinghe, Lichchavi D.; Lock, Adam L.; Harkema, Jack R.; Pestka, James J. (Frontiers in Immunology, 2020)
Lupus is a systemic autoimmune disease typified by uncontrolled inflammation, disruption of im-mune tolerance, and intermittent flaring – events triggerable by environmental factors. Preclinical and clinical studies reveal that consumption of the marine ω-3 highly unsaturated fatty acids (HU-FAs) eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) might be used as a precision nutrition intervention to lessen lupus symptoms. The anti-inflammatory and pro-resolving effects of -3 HUFAs are inextricably linked to their presence in membrane phospholipids. The -3 HUFA score, calculated as [100  (-3 HUFAs/(-3 HUFAs + -6 HUFAs))] in red blood cells (RBCs), and the Omega-3 Index (O3I), calculated as [100  ((DHA+EPA)/total fatty acids)] in RBCs, are two biomarkers potentially amenable to relating tissue HUFA balance to clinical out-comes in individuals with lupus. Using data from three prior preclinical DHA supplementation studies, we tested the hypothesis that the -3 HUFA score and the O3I inversely correlate with indicators of autoimmune pathogenesis in the cSiO2-triggered lupus flaring model. The three studies employed both low and high fat rodent diets, as well as more complex diets emulating the U.S. dietary pattern. The -3 HUFA scores in RBCs were comparatively more robust than the O3I at predicting HUFA balances in the kidney, liver, spleen, and lung. Importantly, increases in both the -3 HUFA score (>40%) and the O3I (>10%) were strongly associated with suppression of cSiO2-triggered 1) expression of interferon-regulated genes, proinflammatory cytokine production, leukocyte infiltration, and ectopic lymphoid structure development in the lung, 2) pulmonary and systemic autoantibody production, and 3) glomerulonephritis. Collectively, these findings identify achievable -3 HUFA scores and O3I thresholds that could be targeted in future human intervention studies querying how -3 HUFA consumption influences lupus and other autoimmune dis-eases.